Biochemical and antioxidant responses of common carp (Cyprinus carpio) exposed to sublethal concentrations of the antiepileptic and analgesic drug gabapentin - J Blahova; P Mikula; P Marsalek; Z Svobodova (Veterinární Medicína)
The present study aimed to evaluate the biochemical and antioxidant responses of common carp after exposure to the antiepileptic and analgesic drug gabapentin at concentrations of 0.1, 1, 10, and 100 μg/l for 4 weeks. The exposure to the highest two concentrations resulted in significant changes in plasma indices such as glucose (only group 100 μg/l), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), lipase, creatine kinase (CK), amylase as well as butyrylcholinesterase (BChE). Similar trends were found in both groups exposed to the environmentally relevant concentrations (i.e., 0.1 and 1 μg/l). In addition, a significant increase in the ferric-reducing power of the plasma was noted in all treated groups. Numerous changes in antioxidant enzymes, superoxide dismutase, catalase, glutathione-S-transferase, as well as lipid peroxidation, were observed especially in the caudal kidney in the group exposed to 100 μg/l. Significant findings were also confirmed in the group exposed to an environmentally relevant concentration (1 μg/l), with a decrease in superoxide dismutase in the gill and an increased lipoperoxidation in the caudal kidney. Our research shows that subchronic exposure to gabapentin may pose a significant risk to non-target aquatic organisms, such as disruption of metabolic pathways or induction of oxidative stress, even at environmentally relevant concentrations.